THSD7B Mutation Induces Platinum Resistance in Small Cell Lung Cancer Patients - Yao Z; Lin A; Yi Y; Shen W; Zhang J; Luo P (Dove Medical Press, 2022)
Zifu Yao,1,2,* Anqi Lin,1,* Yonglin Yi,1,* Weitao Shen,1 Jian Zhang,1 Peng Luo1 1Department of Oncology, Zhujiang Hospital, Southern Medical University, Guangzhou, Guangdong, 510282, People's Republic of China; 2The First Clinical Medical School, Nanfang Hospital, Southern Medical University, Guangzhou, Guangdong, 510515, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhang; Peng Luo, Email zhangjian@i.smu.edu.cn; luopeng@smu.edu.cnAim: Several cases of small cell lung cancer (SCLC) patients demonstrate resistance to the treatment initiatives such as cisplatin after platinum chemotherapy. It is crucial to the improvement of the overall survival (OS) of SCLC patients to discover the gene mutation inducing platinum resistance within this cohort.Patients and Methods: We analyzed the gene mutations significantly associated with the OS from 2 cohorts of SCLC platinum-treated patients. And then we screened out THSD7B mutation. In order to understand the mechanism between THSD7B mutation and platinum resistance, we designed gene mutation co-occurrence and mutual exclusivity analysis, gene set enrichment analysis (GSEA) and gene set variation analysis (GSVA) analysis, and Connectivity Map (CMap) analysis.Results: The poor prognosis of THSD7B mutant patients may be related to the inhibition of cell death-related pathways, the up-regulation of cell invasion and metastasis pathways, and the down-regulation of immune response pathways. Lovastatin and cyclooxygenase inhibitors could be used as potential target compounds in THSD7B mutant patients, which provides reference for future research on platinum resistance.Conclusion: THSD7B can be considered a reliable biomarker that effectively facilitates the prediction of poor survival in SCLC platinum-treated patients.Keywords: small cell lung cancer, gene mutation, platinum, chemotherapy resistance, prognosis